EFEK EKSTRAK BUAH TOMAT (Licopersicum pyriforme) TERHADAP EKSP KOLAGEN TIPE 1, MMP-1 DAN MMP-3 PADA PENUAAN KULIT - Wahyono, Poncojari (Fakultas Kedokteran Universitas Brawijaya, 2008)
ABSTRACT Many theory and research was trying to explain the aging process. Free radical theory explained that allnormal metabolism process in the body can produce free radical.These free radical can destroy the skin cell,and than the skin will start the aging process. The tomato extract has antioxidant such as lycopene, β-carotene and vitamin C. These antioxidant will prevent the activity of free radical, so that skin cell will notdamage. The aims of this research were to study effect of tomato extract juice in preventing skin aging onwistar rats. Total of 25 rats were divided into 5 groups, consisted of 5 rats each. Group one was control groupD-0) rats were four months old, and the group two control of group rats were taken care of 4 months old until7 months old (D-1), the other group which were under treatment classified into 3 groups. Group three wereed 7 g/kg/day/ body weight of tomato fruit extract, then taken care of 4 months old until 7 months old (D-2),group four were fed 11 g/kg/day/ body weight of tomato extract fruit, then taken care of 4 months old until 7months old (D-3) and group five were fed 15 g/kg/day/ body weigh of tomato fruit extract, then taken care of 4months old until 7 months old (D-4).